Exploring contemporary higher education and academic work in Ireland : the impact of policy on practice - Kenny, Aidan (Trinity College (Dublin, Ireland). School of Education, 2010)
The drive for the so called ‘knowledge economy’ and the expected competitive advantage envisioned, has led to 'power elites' and vested interests applying pressure on nation states to develop and implement policies that push the balance of national education systems towards the economic imperative and away from the social good. This thesis will describe ideas, strategies and objectives relating to the pursuit of current higher education change policy agendas, as expressed in key European Union (EU) Education Commission and Council policy documents and communiques and with national strategies, acts and agreements. It provides accounts of other modernisation advocates or 'policy shapers', such as the Organisation for Economic Co-operation and Development (OECD), the World Trade Organisation (WTO) and the World Bank (WB). This thesis concentrates on the modernisation policy agenda relevant to higher education in general, and to academic work: more specifically how this type of work is organised (the labour process ). Critical considerations are given to the tensions that arise between higher education policy formation and implementation and how this affects the academic worker in teaching, research and career. This gap between rhetoric and reality is linked to the dynamic conflict between structure as authoritative bureaucracy and the social action of the academic worker.
Keywords: Education, D.Ed.; Ph.D. Trinity College Dublin